Online ‘chats’: fostering communitas and psychosocial support for people working across arts and play for health and wellbeing - Warran, Katey; Wright, Laura H. V. (Frontiers in Psychology, 2023)
Loss of work, furlough, and increased social isolation were prevalent for many working in the broad context of cultural and community engagement for health and wellbeing. This study set out to explore if and how regular online group interactions may foster social cohesion and provide support for these individuals during the critical time of the COVID-19 global pandemic. It was conducted in the context of the 'social cohesion chat' series led by a network called the Arts Play Health Community which was initiated in response to the pandemic as a way to bring those working in or connected to arts, play and health together during times of social isolation. Two qualitative focus groups with creative, participatory components were conducted with artists, researchers, evaluators, and arts/play managers (n=11), and then analysed using thematic analysis. Researcher ethnographic reflections and fieldnotes were also collected and analysed. The authors engaged in reflexive online discussions to integrate and synthesise findings across different data. Four themes emerged from the analysis procedure: 1) 'Building an online community as processes of communitas', spotlighting the importance of the nonhierarchical structure of the 'chats' particularly in relation to there being 'no end goal' to the online dialogues; 2) 'Individual and shared emotional experiences' that underpinned feelings of connection to others and the online space; 3) 'Psychosocial benefits' such as improving confidence and providing an opportunity to 'have a voice' in the community; and 4) 'The importance of facilitation', highlighting the opportunities the chats provided for participants to feel validated and valued as an active member of the community. The article concludes that constructing an inclusive and welcoming online community, where active participation is at the heart of regular social interactions can provide support for those working across arts and play for health and wellbeing. This was particularly important during the societal turbulence of the COVID-19 pandemic. It further concludes by noting the unique structure of these online dialogues as not being connected to institutions, with this playing a key role in allowing those in the community to 'be themselves' within it.